Trajectories of Preschool Disorders to Full DSM Depression at School Age and Early Adolescence: Continuity of Preschool Depression. - Luby, Joan L.; Gaffrey, Michael S.; Tillman, Rebecca; April, Laura M.; Belden, Andy C. (American Journal of Psychiatry, 2014)
Objective: Preschool-onset depression, a developmentally adapted form of depression arising between ages 3 and 6, has demonstrated numerous validated features, including characteristic alterations in stress reactivity and brain function. This syndrome is characterized by subthreshold DSM criteria for major depressive disorder, raising questions about its clinical significance. To clarify the utility and public health significance of the preschool-onset depression construct, the authors investigated diagnostic outcomes of preschool children at school age and in adolescence. Method: In a longitudinal prospective study of preschool children, the authors assessed the likelihood of meeting full criteria for major depressive disorder at age 6 or later as a function of preschool depression, other preschool axis I disorders, maternal history of depression, nonsupportive parenting, and traumatic life events. Results: Preschool-onset depression emerged as a robust predictor of major depressive disorder in later childhood even after accounting for the effect of maternal history of depression and other risk factors. Preschool-onset conduct disorder also predicted major depression in later childhood, but this association was partially mediated by nonsupportive parenting, reducing by 21% the effect of preschool conduct disorder in predicting major depression. Conclusions: Study findings provide evidence that this preschool depressive syndrome is a robust risk factor for developing full criteria for major depression in later childhood, over and above other established risk factors. The results suggest that attention to preschool depression and conduct disorder in addition to maternal history of depression and exposure to trauma may be important in identifying young children at highest risk for later major depression and applying early interventions.